Using Youtube as a Media to Recite the Quran: A Case Study at Quranic Home Learning Nusantara, Islamic Boarding School Yogyakarta - Wardhany, Adjenk An Nisa Kusuma; Dartim, Dartim; Ayu Larasati, Minten (Universitas Muhammadiyah Surakarta, 2024)
A study on the use of YouTube as a platform to study and memorize the Quran at Quranic Home Learning Nusantara, Islamic Boarding School Yogyakarta can be an interesting research topic. The purpose of this study is to evaluate the extent to which YouTube can support the teaching and learning of the Quran Quranic Home Learning Nusantara, Islamic Boarding School Yogyakarta and analyze the effectiveness of using YouTube as a means of memorizing the Quran in the pesantren. In this context, research will examine the increase in enthusiasm for learning and the effectiveness of learning that occurs with the use of YouTube as a tool for memorizing the Quran. However, in utilizing YouTube, it is important to pay attention to the quality of the content presented, the ease of access to this platform, and the level of mastery of technology by students. In addition, in determining the right learning media, it is necessary to consider other alternatives that suit the needs of students in the pesantren environment, with the aim of improving the quality of Quran teaching.